High incidence of ventricular arrhythmias in patients with left ventricular enlargement and moderate left ventricular dysfunction. Issue 12 (9th September 2016) - Zhao, Shuang; Chen, Keping; Su, Yangang; Hua, Wei; Yang, Jiefu; Chen, Silin; Liang, Zhaoguang; Xu, Wei; Zhang, Shu
Abstract : Background: Left ventricular ejection fraction (LVEF) ≤35% is the cutoff value used to identify patients at high risk of sudden cardiac death. However, whether patients who have moderate left ventricular dysfunction and left ventricular enlargement (LVE) have a high risk of ventricular arrhythmias (VAs) and cardiac death is unclear. Hypothesis: Patients with moderate left ventricular dysfunction and LVE may have a high risk of VAs. Methods: This study retrospectively analyzed the data of 853 patients who have an implantable cardioverter‐defibrillator/cardiac resynchronization therapy cardioverter‐defibrillator equipped with home monitoring. The patients were divided into 4 groups: group A, 35% < LVEF ≤ 45% and left ventricular end‐diastolic dimension (LVEDD) ≥60 mm; group B, LVEF ≤35% and LVEDD <60 mm; group C, 35% < LVEF ≤ 45% and LVEDD <60 mm; and group D, LVEF ≤35% and LVEDD ≥60 mm. Results: During a mean follow‐up period of 30 ± 13 months, 324 patients (38%) experienced VAs and 125 patients (14.7%) experienced cardiac death. Based on multivariate Cox regression modeling, group A had an increased risk of VAs (A vs B, hazard ratio [HR]: 1.563, 95% confidence interval [CI]: 1.029‐2.375, P = 0.036; A vs C, HR: 1.661, 95% CI: 1.204‐2.294, P = 0.002) and cardiac death (A vs B, HR: 1.845, 95% CI: 1.013‐3.356; A vs C, HR: 2.041, 95% CI: 1.136‐3.731, P = 0.021). Conclusions: Patients with moderate left ventricular dysfunction and LVE have a high risk of VAs and cardiac death.